"You Still Believe Like a Jew!": Polemical Comparisons and Other Eastern Christian Rhetoric Associating Muslims with Jews from the Seventh to Ninth Centuries - Freidenreich, David M. (Entangled Religions, 2020)
Patriarch Timothy I and Theodore bar Koni, late eighth-century members of the Church of the East, brand Muslims as "new Jews," in Timothy’s words, on account of their refusal to accept Christian doctrines about Christ. Like many other Eastern Christians, these authors employ the discourse of anti-Judaism against Muslim targets to reinforce the faith of their Christian audiences. Timothy and Theodore, however, are the only known authors of the initial Islamic centuries who employ the rhetorical device of polemical comparison when associating Muslims with Jews. Analysis of the elements with which Timothy and Theodore construct their comparisons reveals the goals that they hoped to achieve through their innovative use of traditional anti-Jewish discourse as well as the distinctive contributions of this rhetorical device to their arguments on behalf of Christian truth claims. This essay demonstrates a broadly applicable method for rhetorical analysis of polemical comparisons.